Segmenting, Targeting, and Positioning Strategies in Attracting the Interest of Students in Learning Nahwu - Umar Manshur; Hasan Baharun; Dakir Dakir; Zadana Bil Mahasini (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2023)
This research aims to analyze Segmenting, Targeting, and Positioning (STP) strategies to attract the interest of students studying Nahwu at the Nurul Jadid Islamic Boarding School, Probolinggo, East Java, Indonesia. This research uses a qualitative approach with a case study type of research. Researchers conducted observations, in-depth interviews, and documentation to obtain accurate, valid, and accountable data. Data analysis was carried out systemically, starting from data reduction, data presentation, and drawing research conclusions. This research shows that segmenting, targeting, and positioning, mapping, and placing students in learning Nahwu science is very important so that learning can provide comfortable and meaningful conditions for students; this can increase students' interest in studying Nahwu science. This research provides implications regarding the importance of appropriate segmentation, targeting, and positioning in learning Nahwu science so that educational institutions can increase students' interest in learning and involvement in studying Nahwu science more effectively, excitingly, and meaningfully so that learning objectives can be achieved maximally.